Entrepreneurial Motivation and Idea Generation by Displaced Employees - Källner, Emelie; Nyström, Kristina (Senate Hall, 2018)
This paper studies the entrepreneurial motivation and idea generation process of displaced employees. The empirical results are based on both quantitative (survey) and qualitative (interviews) data collected from displaced employees who decided to become entrepreneurs after the closure of R&D facilities of the pharmaceutical company AstraZeneca in Lund (2010) and Södertälje (2012), Sweden. The empirical findings show that the previous experience and expertise gained from AstraZeneca greatly influenced the idea generation process. Although the employees were affected by their job displacement, still 70 percent of the entrepreneurial activities could be regarded as opportunity-based, suggesting that many entrepreneurs are driven by a combination of push and pull motives. With regard to the timing of the idea generation process, about one third of the entrepreneurs came up with their business ideas before learning about the facility closures. Hence, in many cases, being affected by the displacement spurred the launch of ideas that already existed. Keywords: entrepreneurship, firm closure, firm exit, entrepreneurship after displacement, entrepreneurial idea generation. JEL Codes: J63, L26
Keywords: entrepreneurship|firm closure|firm exit|entrepreneurship after displacement|entrepreneurial idea generation